Democratic directionality for transformative food systems research - Duncan, Jessica; DeClerck, Fabrice A.J.; Báldi, András; Treyer, Sébastien; Aschemann-Witzel, Jessica; Cuhls, Kerstin; Ahrné, Lilia; Bisoffi, Stefano; Grando, Stefano; Guobys, Liutauras; Kohl, Johanna; Otte Hansen, Henning; et al. (Springer, 2022)
Effective interfaces of knowledge and policy are critical for food system transformation. Here, an expert group assembled to explore research needs towards a safe and just food system put forward principles to guide relations between society, science, knowledge, policy and politics.